2015
DOI: 10.1111/anu.12337
|View full text |Cite
|
Sign up to set email alerts
|

Optimal dietary alpha-linolenic acid/linoleic acid ratio improved digestive and absorptive capacities and target of rapamycin gene expression of juvenile grass carp (Ctenopharyngodon idellus)

Abstract: Growth performance, digestive and absorptive capacities and target of rapamycin (TOR), ribosomal protein S6 kinase 1 (S6K1) and eIF4E-binding protein (4E-BP) gene expression in the hepatopancreas and intestine of juvenile grass carp (Ctenopharyngodon idellus) fed graded ratios of dietary alpha-linolenic acid/linoleic acid (ALA/LNA) (0.01, 0.34, 0.68, 1.03, 1.41, 1.76 and 2.15) for 60 days were investigated. The results showed that ALA/LNA ratio of 1.03 significantly improved (i) per cent weight gain (PWG) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 84 publications
1
46
0
Order By: Relevance
“…Not only that, it was reported that the growth of fish was also positively related to the ability of nutrients uptake in the intestines, which could be partly influenced by intestinal morphology(Olsen et al, ; Zeng et al, ). The blood capillary hyperaemia was an important part of intestinal morphology in fish (Zheng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Not only that, it was reported that the growth of fish was also positively related to the ability of nutrients uptake in the intestines, which could be partly influenced by intestinal morphology(Olsen et al, ; Zeng et al, ). The blood capillary hyperaemia was an important part of intestinal morphology in fish (Zheng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, we next investigated effects of ETSP on fish digestive and absorptive ability. Supplementation of ETSP in the low-protein diet enhanced hepatopancreas and intestinal development and digestive and brush border enzyme activities of fish To our knowledge, fish digestive and absorptive capacity is closely related to the growth and function of digestive organs as well as the activities of digestive enzymes (trypsin, chymotrypsin, lipase, and amylase) and brush border enzymes (AKP, Na + /K + -ATPase, γ-GT, and CK) (Lin and Zhou 2006;Zeng et al 2015). The present study showed that decrease of 2% dietary protein (dietary protein level from 34 to 32%) decreased the HW, IL, RGL, IW, ISI, IPC, fold heights in MI and DI, as well as activities of most digestive enzymes in intestine and hepatopancreas and brush border enzymes in intestine, whereas adding 10 g/kg ETSP to the low-protein diet reversed these negative effects by low dietary protein level.…”
Section: Discussionmentioning
confidence: 99%
“…However, the detailed mechanisms require further investigation. In fish, the gene expression of brush border enzymes may be regulated by TOR signaling pathway (Zeng et al 2015). Li et al (2016) suggested that the upregulation of TOR molecule stimulated intestinal brush border enzyme gene expression in grass carp.…”
Section: Discussionmentioning
confidence: 99%
“…The biotransformation pathway of methyl 2-methylvalerate should be confirmed by radioactive isotope labeling experiment. Linolenic acid as the important member of fatty acids had been considered as the essential fatty acids (Zeng et al 2015), which could be transformed perhaps from n-hexadecanoic acid as showed in Table 1. The increases of linolenic acid should also improve the quality of vine tea.…”
Section: Discussionmentioning
confidence: 99%